Structural characteristics of transtensional fault system and its implication for hydrocarbon accumulation in s block, south asia area - Dong, Y. (TUBITAK, 2021)
Transtensional faults are well developed in the S Block of the South Asia area, which have an important impact on the hydrocarbon accumulation. However, the transtensional fault structure is very complex. Based on drilling and seismic data interpretation results, faults are divided into three typical types in the Lower Cretaceous, which can help to understand the complex fault system. The main faults are distributed in the NNW-SSE direction and parallel arrangement with dextral strike-slip shear characteristics, which determines the development of the tectonic belt. The secondary faults are often associated with the main faults, often composed of multiple branch faults. The complexity of the fault system is further aggravated by the small interlayer faults. Based on balanced cross-section technique analysis, the fault evolution has experienced five geological periods, which is closely related to the Indo-Pakistan plate tectonics and the Indus Basin evolution. In the diagonal extension stage of the Late Cretaceous, the fault activity was very strong, which had a significant impact on the tectonic pattern of âhorst-graben structures and locally complex faulted blocksâ in S Block. It is found that transtensional fault assemblage patterns are regular and diverse. It consists of six kinds of plane assemblage and seven kinds of profile assemblage patterns. Plane assemblage patterns include en echelon, broom, feather, comb, horsetail and diamond shape, while profile assemblage patterns consist of horst-graben faulted type, consequent faulted type, antithetic faulted type, âYâ and reverse âYâ type, âXâ type and negative flower type. Different transtensional fault assemblage patterns form various kinds of hydrocarbon trap types, including faulted block, faulted nose, faulted anticline and composite traps. Fault activity and evolution promote the hydrocarbon generation, control the formation of tectonic zones and favorable traps and play an important control role in hydrocarbon migration and accumulation. Therefore, in this study the main exploration and evaluation targets are faulted reservoirs in the study area. Â© TÃBÄ°TAK.